Pelatihan Workshop Membangun Bank Sampah dan Pengelolaan Sampah - Dina Azilia Ramadhani; Liya Andriyani; Veva Farika (CV. KAMPUS AKADEMIK PUBLISING, 2024)
he waste problem is one of the most pressing environmental issues in Indonesia. The increasing volume of waste every year, especially in urban areas, has had a negative impact on the environment and public health. Therefore, this training carries the theme of a workshop on building waste banks and waste management as a means for people to care more about the environment. This activity was attended by 24 participants from KONI athletes and the general public. From the results of this activity, participants felt that this workshop was very useful, seen from the post-test score of 100%.